2017
DOI: 10.1002/cam4.1237
|View full text |Cite
|
Sign up to set email alerts
|

SMG‐1 inhibition by miR‐192/‐215 causes epithelial‐mesenchymal transition in gastric carcinogenesis via activation of Wnt signaling

Abstract: SMG‐1,a member of the phosphoinositide kinase‐like kinase family, functioned as a tumor suppressor gene. However, the role of SMG‐1 in GC remain uncharacterized. In this study, regulation of SMG‐1 by miR‐192 and‐215, along with the biological effects of this modulation, were studied in GC. We used gene microarrays to screening and luciferase reporter assays were to verify the potential targets of miR‐192 and‐215. Tissue microarrays analyses were applied to measure the levels of SMG‐1 in GC tissues. Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
2
24
1
Order By: Relevance
“…MicroRNA is an endogenous 18-24 nucleotide (nt) single stranded RNA molecule, which is a transcription regulator of gene expression [16]. It can stabilize target messenger RNA transcriptase by inhibiting the translation process or the cracking of target messenger RNA [17]. Nowadays, a growing body of studies have revealed that miRNAs are involved in DNA damage and repair, apoptosis regulation, cell cycle regulation and so on [18].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA is an endogenous 18-24 nucleotide (nt) single stranded RNA molecule, which is a transcription regulator of gene expression [16]. It can stabilize target messenger RNA transcriptase by inhibiting the translation process or the cracking of target messenger RNA [17]. Nowadays, a growing body of studies have revealed that miRNAs are involved in DNA damage and repair, apoptosis regulation, cell cycle regulation and so on [18].…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that miRNAs probably play a significant role in GC. Furthermore, in the previous study, we have verified that miRNA‐192 and miRNA‐215 are upregulated in GC, exerting an effect of facilitating cell growth and cell migration (Jin et al, 2011; X. Zhang et al, 2018a, 2018b).…”
Section: Introductionmentioning
confidence: 58%
“…As shown in Figure 4, cell proliferation was repressed by miRNA‐192 and ‐215 inhibitors, however, APC siRNAs enhanced the multiplication capacity compared with those in groups transfected with miRNA‐192 or ‐215 inhibitors only (Figure 4a). In the previous study, we have proved that suppression of either miRNA‐192 or ‐215 plays an inhibitory effect on migration (Jin et al, 2011; X. Zhang et al, 2018a, 2018b). Base on the previous work, SGC7901 cells were contransfected with miRNA‐192 and ‐215 inhibitors and APC siRNAs, respectively.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, Zhang et al . 30 showed that miR-192/215 can also act as oncomirs promoting epithelial-mesenchymal transition in gastric cancer repressing the tumor suppressor gene nonsense mediated mRNA decay associated PI3K related kinase ( SMG1 ). These findings suggest that the miR192/215 family miRNAs may exert oncogenic functions in mucinous carcinomas.…”
Section: Discussionmentioning
confidence: 99%